2022
DOI: 10.1186/s12889-022-13062-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of socioeconomic status on the physical and mental health of the elderly: the mediating effect of social participation

Abstract: Background Previous studies have demonstrated the effect of socioeconomic status on the health status of the elderly. Nevertheless, the specific dimensions of the effect and the mechanism await further investigation. In this study, socioeconomic status was divided into three dimensions and we used social participation as the mediation variable to investigate the specific path of effect. Methods Using the 2018 Waves of Chinese Longitudinal Healthy L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Potential differences exist between populations in different regions, including living environment and dietary habits. Moreover, people with higher education and per capita income have higher health literacy and will pay more attention to their health (23)(24)(25)(26). The analysis revealed certain patterns of morbidity, mortality, and DALYs varying across SDI regions.…”
Section: Discussionmentioning
confidence: 99%
“…Potential differences exist between populations in different regions, including living environment and dietary habits. Moreover, people with higher education and per capita income have higher health literacy and will pay more attention to their health (23)(24)(25)(26). The analysis revealed certain patterns of morbidity, mortality, and DALYs varying across SDI regions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that anxiety disorders are more common in later life; there is some evidence that anxiety disorders are associated with lower levels of education ( 39 ). Grossman's theory of health production suggests that health is influenced by healthcare, income level, lifestyle, education level, and living environment ( 40 ). There is a close link between an individual's education level and their health ( 41 , 42 ).…”
Section: Challenges Of Oaementioning
confidence: 99%
“…However, the current lack of outreach capacity and insufficient supply of OAE are problems that continue to restrict the development of OAE. To increase the motivation of older adults to participate in OAE ( 40 ), countries should formulate a series of support strategies for developing OAE according to national conditions; such strategies will enable OAE to be fully valued by older adults. The promotion of OAE involves broadening channels, increase government investment in OAE at all levels, introduce social capital, and use internet resources and television news for publicity.…”
Section: Challenges Of Oaementioning
confidence: 99%
“…Current research on the influencing factors of the physical and mental health of the elderly has been comprehensive and in depth. It covers living habits, Internet use, sleep quality, diet quality, physical activity, family intergenerational support, personal ability, social welfare, social economy, social participation, and social support (9)(10)(11)(12)(13)(14)(15)(16). The existing research has made a comprehensive observation on the influencing factors of physical and mental health.…”
Section: Introductionmentioning
confidence: 99%